THE GASTROPROTECTIVE AND ANTIOXIDANT EFFECT OF BELLIS PERENNIS L. (ASTERACEAE) EXTRACTS - Acik, L.; Gurbuz, I; Demir, H.; Demirci, F. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Bellis perennis is used in Turkish folk medicine against various diseases including peptic ulcer [1-2]. In order to confirm the claimed activity on peptic ulcer, aqueous and methanol extracts were prepared from the aerial parts of the material. Both extracts were tested for their anti-ulcerogenic potential on the ethanol-induced gastric ulcer model using rats. The aqueous and methanol extracts were administered orally at 1100 and 600 mg/kg doses, respectively, where both extracts demonstrated significant anti-ulcerogenic activity statistically (p<0.001). Additionally, the antioxidant potential of the extracts was evaluated by DPPH free radical scavenging and total antioxidant capacity methods. The results showed that B. perennis extracts can be used as a good potential source of natural antioxidants. Chromatographic fingerprints and constituents of these extracts were also documented using LC and LC-MS techniques. Further studies are needed in order to isolate and define the active constituent(s).